Physicians' assessment of the Bavarian drug-expenditure control system: a qualitative study - Nikoletta Zeschick; Julia Gollnick; Julia Muth; Franziska Hörbrand; Peter Killian; Norbert Donner-Banzhoff; Thomas Kühlein; Maria Sebastião (BMC, 2023)
Abstract Background In 2014 a new system for drug expenditures, the Wirkstoffvereinbarung (WSV, English: Active substance agreement) was implemented in Bavaria. In pre-defined indication groups, economic prescription of medications shall be enabled based on the selection, quantity, and proportion of an individual drug. Ambulatory care physicians receive quarterly trend reports on their prescribing behavior. This study examines physicians' perceptions of the WSV. Methods Qualitative interviews (n = 20) and seven focus groups (n = 36) were conducted with ambulatory care physicians (e.g. general practitioners, cardiologists, pulmonologists). The methodology followed Qualitative Content Analysis. Results Physicians generally accepted the necessity of prescribing economically. The majority of them rated the WSV positively and better than the previous system. As an improvement, they especially named timely feedback in form of easily understandable trend reports, encouraging self-reflection as well as allowing early control options. Problems perceived were drug discount contracts that were strongly criticized as leading to patients mixing up medications. Some perceived constraints of therapeutic freedom. Conclusions The implementation of the WSV is mostly viewed positively by physicians. The restrictions of therapeutic freedom partially perceived might be met by improved information on the reasons why some drugs are rated as less economical than others. Trial registration number Main ID: DRKS00019820 (German Register of Clinical Studies and World Health Organization).